EFFECTIVE WAYS TO ORGANIZE INVESTMENT COMPANIES BASED ON SERVING ISLAMIC FINANCIAL SERVICES IN COMMERCIAL BANKS - Yuldasheva Madinaxon Mamasadikovna (Ecominds Press, 2025)
The article discusses the history and development of the Islamic Finance, as well as the main directions for organizing investment companies based on serving Islamic financial services in commercial banks of the Republic of Uzbekistan.
Keywords: Islamic finance, Islamic banking, European Banking Union, Islamic financial products, Islamic financial institutions, Banking system, Shariah.